2002
DOI: 10.1007/s00210-002-0578-2
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 receptor antagonists reduce cardiac electrical instability induced by high glucose in rats

Abstract: Endothelin-1 (ET-1) influences the electrical activity of the heart by causing arrhythmias associated with lengthening of the QT interval in the electrocardiogram. Recent results from our laboratory have shown a primary role for a high plasma glucose concentration in determining cardiac QT prolongation. Since high glucose up-regulates the ET-1 system, the aim of the present study was to determine whether the increase of the QT interval and coronary vascular tone induced by high glucose in the heart involves in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Marfella et al described for the first time the effect of acute hyperglycemia on QTc duration in healthy men [ 27 ]. D’Amico et al in 2001 demonstrated that high glucose levels into the heart induce ventricular instability characterized by QT interval prolongation [ 8 ], an evidence subsequently continued by Di Filippo et al, in 2002 [ 28 ]. More appropriately, Morales-Cano et al, found that hyperglycemia down-regulates KV7 potassium channels at the level of coronary artery influencing their reactivity [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marfella et al described for the first time the effect of acute hyperglycemia on QTc duration in healthy men [ 27 ]. D’Amico et al in 2001 demonstrated that high glucose levels into the heart induce ventricular instability characterized by QT interval prolongation [ 8 ], an evidence subsequently continued by Di Filippo et al, in 2002 [ 28 ]. More appropriately, Morales-Cano et al, found that hyperglycemia down-regulates KV7 potassium channels at the level of coronary artery influencing their reactivity [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia was found to impair the human ether‐a‐go‐go‐related gene (HERG) function by reducing HERG current, and causing significant increases in the intracellular levels of reactive oxygen species 26 . Additionally, hyperglycemia has been shown to upregulate endothelin‐1 levels, which may contribute to electrical instability in the heart 27 …”
Section: Introductionmentioning
confidence: 99%
“…Of these, 12 were excluded having a sinus rate of <210 beats per minute or a coronary perfusion pressure (CPP) <60 mmHg between 5 and 15 min after beginning of the perfusion; hearts not in sinus rhythm during the study were also excluded. The remaining 70 hearts having a sinus rate of >210 beats per minute or CPP > 60 mmHg, between 5 and 15 min after beginning, were used in the study and divided into the following experimental groups ( n = 10 rats for each group): (i) control: hearts perfused for 2 hours with a Krebs solution containing D-glucose at 11.1 mM [ 4 , 5 ]; (ii) high glu: hearts perfused for 2 hours with Krebs solution containing D-glucose at 33.3 mM [ 4 , 5 ]; (iii) high glu + DMSO: hearts perfused with Krebs solution containing 1% DMSO + D-glucose at 33.3 mM; (iv) high glu + BF-5m: hearts perfused for 2 hours with Krebs solution containing D-glucose at 33.3 mM + BF-5m (0.01 μ M in 1% DMSO); (v) high glu + BF-5m: hearts perfused for 2 hours with Krebs solution containing D-glucose at 33.3 mM + BF-5m (0.05 μ M, in 1% DMSO); (vi) high glu + BF-5m: hearts perfused for two hours with Krebs solution containing D-glucose at 33.3 mM + BF-5m (0.1 μ M, in 1% DMSO). Moreover, in order to assess the role of SIRT1 in the BF-5m cardiac effects additional studies were done on 10 hearts excised from rats pretreated for 7 days (10 mg/kg/day i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Temperature was maintained constant by means of a heated (37°C) water jacket. On establishing a stable value (20–30 min following cannulation) CPP was calculated according to Di Filippo et al [ 4 ]. Briefly, CPP value was expressed either as the mean of each 10-min value throughout the entire experiment or as the mean of the steady-state increment above baseline when an increase of CPP was evident during an experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation